2018
DOI: 10.1108/rausp-04-2018-006
|View full text |Cite
|
Sign up to set email alerts
|

Taxation, corporate governance and dividend policy in Brazil

Abstract: Purpose-This study aims to analyze the influence of taxes and corporate governance on the dividend policy of Brazilian companies. Design/methodology/approach-The authors identify the changes of the tax legislation in Brazil in the period 1986-2011 and check their effect on corporate dividend policies for preferred and common shares. The authors use panel data Probit and Tobit estimation to verify the probability of companies to pay dividends under different tax regimes. The final sample comprises 672 companies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
(20 reference statements)
1
5
0
4
Order By: Relevance
“…The overall findings of the secondary data analysis indicate that a positive relation between the corporate governance index and both the propensity to pay dividends and dividend payout. Hence, the results are broadly consistent with the outcome model of dividends instead of the substitute model as reported in by Yarram (2015), Yarram and Shamsabadi et al (2016) in Australia, Zagonel et al (2018) in Brazil, Abor and Fiador (2013) in Ghana, Kenya and South Africa and Roy (2015) in India. Our complementary findings are broadly consistent with agency theory to lessen agency concerns.…”
Section: Data Analysis and Discussionsupporting
confidence: 88%
“…The overall findings of the secondary data analysis indicate that a positive relation between the corporate governance index and both the propensity to pay dividends and dividend payout. Hence, the results are broadly consistent with the outcome model of dividends instead of the substitute model as reported in by Yarram (2015), Yarram and Shamsabadi et al (2016) in Australia, Zagonel et al (2018) in Brazil, Abor and Fiador (2013) in Ghana, Kenya and South Africa and Roy (2015) in India. Our complementary findings are broadly consistent with agency theory to lessen agency concerns.…”
Section: Data Analysis and Discussionsupporting
confidence: 88%
“…In a paper by T. Zagonel et al (2018), based on a sample of 672 companies whose shares were listed on the São Paulo Stock Exchange in the period from 1986 to 2011 (a total of 30,134 observations), the authors conclude that companies in the Brazilian market do not strive for a target dividend payout ratio. At the same time, the authors revealed a direct correlation between current dividends and dividends in the previous period.…”
Section: Hypotheses On the Impact Of The Quality Of Corporate Governance On Dividend Policy In The Brics Countriesmentioning
confidence: 99%
“…This theory focuses on agency conflicts between managers and shareholders, and, thus, dividend payments help reduce the agency costs associated with the separation of management and ownership (Ozo et al, 2015). Hence, the agency conflict between managers and shareholders may be responsible for the adoption of non-maximizing shareholders' wealth dividend policies (Zagonel, Terra, & Pasuch, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%